الأحكام الفقهية المتعلقة بوباء كورونا في الأحوال الشخصية "النكاح والطلاق والنفقة" - السويداء، مها بنت سالم بن إبراهيم (جامعة الأزهر - كلية الشريعة والقانون بتفهنا الأشراف - دقهلية, 2020)
الحمد لله رب العالمين، والعاقبة للمتقين، والصلاة والسلام على عبده ورسوله وخليله، وأمينه على وحيه، وصفوته من خلقه نبينا محمد بن عبد الله، وعلى آله وصحبه، ومن سلك سبيله، واهتدى بهداه إلى يوم الدين، أما بعد: فقد اهتم الفقهاء قديماً وحديثاً بدراسة النوازل في كل عصر وحين، تأصيلاً وتكييفاً بما يناسب الحال والمآل، ومن تتبع مصادر الفقه ومراجعه سيقف لا شك على ذلك التراث، وتلك الجهود. ومما يعد من نوازل عصرنا وباء كورونا المسمى -(Covid 19) حمى الله البلاد والعباد منه - . وقد تضافرت الجهود التي تبذلها حكومة المملكة العربية السعودية - حرسها الله - في مواجهة هذا الوباء، أمنياً، وصحياً، وعلمياً، فقد بذلت في سبيل ذلك ما يذكر فيشكر، ومن تلك الجهود: حث الجامعات والجهات ذات العلاقة، والباحثين والباحثات للمساهمة في حلول تكاملية في هذا الشأن. الأمر الذي تطلب من الباحثين وأهل العلم الشرعي: المساهمة في بيان هذه الأحكام الشرعية، ومن هنا رأت الباحثة - بعد استخارة واستشارة- المساهمة في هذه الجهود قياماً بواجبها الوطني والعلمي، فكانت هذه الدراسة بعنوان: (الأحكام الفقهية المتعلقة بوباء كورونا في الأحوال الشخصية -النكاح، والطلاق، والنفقة)، والتي اشتملت على مقدمة، وأربعة مباحث، وخاتمة. فنسأل الله سبحانه أن يرفع عن الأمة الإسلامية الوباء والبلاء، وأن يوفقنا في هذا العمل وأن يجعله خالصا لوجهه الكريم.
Praise be to God, the Lord of the worlds, and the punishment for the righteous, and blessings and peace be upon his servant, messenger and concubine, and his trustee on his revelation, and the elite of his creation, our Prophet Muhammad bin Abdullah, his family and companions, and those who followed his path, and guided his guidance until the Day of Judgment. The jurists, in the past and present, have been concerned with studying the calamities in every age and time, establishing and adapting them to suit the situation and prospects, and whoever follows the sources of jurisprudence and its references will undoubtedly stand on that heritage and those efforts. And what is considered one of the woes of our time is the Corona epidemic called (Covid 19) - may God protect the country and its people from it. The government of the Kingdom of Saudi Arabia - may God protect it - has concerted efforts to confront this epidemic, in terms of security, health, and science. For this it has made what is mentioned and thankful, and among those efforts: Urging universities and the relevant authorities, researchers and researchers to contribute to integrative solutions in that matter. The matter that required researchers and people of legal knowledge: to contribute to clarifying these Sharia rulings, and from here the researcher - after seeking advice and advice - decided to contribute to these efforts in fulfillment of her national and scientific duty., Divorce, and alimony), which included an introduction, four investigations, and a conclusion. We ask God, may He be glorified, to lift the plague and affliction from the Islamic Ummah, to guide us in this work and to make it sincere for His honorable sake.
Keywords: الشريعة الإسلامية -- الأحكام الفقهية -- الأحوال الشخصية -- وباء كورونا